Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Loyalitas Pelanggan Dengan Sertifikasi Halal Sebagai Variabel Moderasi di Pesawaran - Resta Uke Yurinda; Rina El Maza; Carmidah Carmidah (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of service quality and product quality on customer loyalty, with halal certification as a moderating variable at CV Madun Ayam in Pesawaran Regency. The study population consisted of 723 customers, with a sample of 88 respondents determined using the Slovin formula. Data were analyzed using SmartPLS 3 and Structural Equation Modeling–Partial Least Squares (SEM-PLS). Customer loyalty was positively and significantly influenced by service and product quality, with product quality being the most important aspect, based on research findings. Conversely, halal certification did not significantly impact customer loyalty and did not act as a moderating variable. These findings indicate that customer loyalty is more driven by service and product quality, while halal certification is perceived as a basic attribute supporting trust.